Ilexsaponin A1 Ameliorates Diet-Induced Nonalcoholic Fatty Liver Disease by Regulating Bile Acid Metabolism in Mice - Zhao, Wen-wen; Xiao, Meng; Wu, Xia; Li, Xiu-wei; Li, Xiao-xi; Zhao, Ting; Yu, Lan; Chen, Xiao-qing (Frontiers in Pharmacology, 2021)
Bile acid (BA) metabolism is an attractive therapeutic target in non-alcoholic fatty liver disease (NAFLD). We aimed to investigate the effect of Ilexsaponin A1 (IsA), a major bioactive ingredient of Ilex L., on high-fat diet (HFD) induced NAFLD in mice with a focus on BA homeostasis. Male C57BL/6J mice were fed a HFD to induce NAFLD and were treated with IsA (120 mg/kg) for 8 weeks. The results showed that administration of IsA significantly decreased serum total cholesterol (TC), attenuated liver steatosis, and decreased total hepatic BA levels in HFD induced NAFLD mice. IsA-treated mice showed increased BA synthesis in the alternative pathway by upregulating the gene expression levels of sterol 27-hydroxylase (CYP27A1) and cholesterol 7b-hydroxylase (CYP7B1). IsA treatment accelerated efflux and decreased uptake of BA in liver by increasing hepatic farnesoid X receptor (FXR) and bile salt export pump (BSEP) expression, and reducing Na+-taurocholic acid co-transporting polypeptide (NTCP) expression. Alterations in the gut microbiota and increased bile salt hydrolase (BSH) activity might be related to enhanced fecal BA excretion in IsA-treated mice. This study demonstrates that consumption of IsA may prevent HFD-induced NAFLD and exert cholesterol-lowering effects, possibly by regulating the gut microbiota and BA metabolism.